Тәлим системасы сыпатын көтериў бүгинги күнниң актуаль мәселелеринен бири сыпатында (FAN va JAMIYAT, 2018)
The article is devoted to the description of existing education quality assessment systems and their conditional separa- tion into two groups based on their external or internal assessment: the French model based on the external model and the Englisn, based on internal assessments.